ANALISIS YURIDIS PERTANGGUNGJAWABAN HUKUM PENYELENGGARA PERDAGANGAN MELALUI SISTEM ELEKTRONIK TERHADAP BARANG YANG TIDAK SAMPAI - Gabriel Gloria; Jeane Neltje Saly (Jurnal Hukum Adigama, 2020)
The marketplace as an organizer of trade through an electronic system is a forum that bridges by providing convenience for online buying and selling activities. This study aims to determine the legal relationship between the parties involved in buying and selling activities and to find out how the accountability of trade organizers through electronic systems for goods that do not arrive. This type of research used in this research is normative legal research. The legal relationship in buying and selling is a continuous and mutually sustainable relationship because they need each other. In the event that an order does not reach the marketplace as a trade organizer through an electronic system is not responsible because he will be responsible if the loss arises from services used such as hacked data, then to obtain legal certainty the consumer can appoint another appropriate party, namely the merchant to be held accountable. compensation.